DHOMIR ON THE MOSES STORY IN AL QUR’AN SURAA AT-THAHA - Dian Cahyo Kurniawan; Nababan Nababan; Riyadi Santosa (Universitas Sebelas Maret, 2017)
In Arabic, dhomir is divided into : Munfashil, namely 1st person (Mutakallim) pronoun that can be stand as autonomous word. And Muttasil, is 2nd person (Mukhotob) and 3rd person (Ghaibun), which embeeded after the word. and their form are used for singular, two person and plural. The objectives of this research is the form of dhomir that representing the main characters in the story. Here, dhomir are subtitutes characters such as: Alloh Al Mighty, Moses, Aaron, Pharaoh, and Israelian. As conclusion, dhomir clearly summarize or ihtisar of the pronoun of Alloh, Moses Aaron and Pharaoh.